Comparison of EMG Activation of Tricpes Brachii and Serratus Anterior Muscle during Push-Up Exercise on Supported Surfaces - Kim, So-Hee; Lee, Su-Young (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to identify the effect of push-up exercise upon the sling and fixed surface on the triceps brachii and serratus anterior muscle activation.Methods/Statistical analysis: Twenty healthy subjects agreed to the participation of this experiment and were those who met with the selection criteria. The subjects performed randomly the static and dynamic push-up exercise on the fixed surface, and the static and dynamic push-up exercise on the sling. While each push-up exercise was conducted on the surfaces, the triceps brachii and serratus anterior muscle activation was measured by surface electromyography (sEMG). Repeated ANOVA was used to compare the mean of EMG activation of the triceps brachii and serratus anterior muscle normalized by maximal voluntary isometric exercise.Findings: The result showed that there was significantly different in triceps brachii long head muscle activation within the measure (p.05). The triceps brachii muscle activity showed a significant increase in the static push-up exercise upon the sling compared to the dynamic push-up exercise on the fixed surface and sling (p.05).Improvements/Applications: These findings suggest that static push-up exercise on sling can strengthen the triceps brachii long head muscle more effectively than the triceps brachii lateral head. That is necessary for the use of walker and wheelchair in patients with paraplegia.